Colorful Conductive Threads for Wearable Electronics: Transparent Cu–Ag Nanonets. Issue 24 (15th July 2022) - Tang, Yan; Guo, Bin; Cruz, Mutya A.; Chen, Han; Zhou, Qicheng; Lin, Zefeng; Xu, Fuchun; Xu, Feiya; Chen, Xiaohong; Cai, Duanjun; Wiley, Benjamin J.; Kang, Junyong
Abstract: Electronic textiles have been regarded as the basic building blocks for constructing a new generation of wearable electronics. However, the electronization of textiles often changes their original properties such as color, softness, glossiness, or flexibility. Here a rapid room‐temperature fabrication method toward conductive colorful threads and fabrics with Ag‐coated Cu (Cu‐Ag) nanonets is demonstrated. Cu–Ag core–shell nanowires are produced through a one‐pot synthesis followed by electroless deposition. According to the balance of draining and entraining forces, a fast dip‐withdraw process in a volatile solution is developed to tightly wrap Cu–Ag nanonets onto the fibers of thread. The modified threads are not only conductive, but they also retain their original features with enhanced mechanical stability and dry‐wash durability. Furthermore, various e‐textile devices are fabricated such as a fabric heater, touch screen gloves, a wearable real‐time temperature sensor, and warm fabrics against infrared thermal dissipation. These high quality and colorful conductive textiles will provide powerful materials for promoting next‐generation applications in wearable electronics. Abstract : Various types of colorful threads have been modified into conductive by wrapping with Cu‐Ag nanonets without losing their original features. The conductive threads show excellent mechanical stability, dry‐wash durability and sewability. E‐textile devices such as fabric heater, touch screen gloves, temperature sensing cloth, and warm fabrics are fabricated for smart‐fabric applications.